Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21037/tgh.2020.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser endomicroscopy in gastro-intestinal endoscopy: technical aspects and clinical applications

Abstract: Confocal laser endomicroscopy (CLE) is an advanced endoscopic imaging technology that provides a magnified, cellular level view of gastrointestinal epithelia. In conjunction with topical or intravenous fluorescent dyes, CLE allows for an "optical biopsy" for real-time diagnosis. Two different CLE system have been used in clinical endoscopy, probe-based CLE (pCLE) and endoscope-based CLE (eCLE). Using pCLE, the device can be delivered: (I) into the luminal gastrointestinal tract through the working channel of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 96 publications
0
37
0
Order By: Relevance
“…The term confocal refers to the alignment of the light source and the collection system in the same specimen plane. After the laser illuminates the specimen, the tissue emits fluorescence, which is detected by the collection system for image generation (25). The current generation CLE device we used was designed specifically to be integrated into the Bar chart showing a comparison of overall mean (SD) brightness and contrast of in vivo and ex vivo images.…”
Section: Discussionmentioning
confidence: 99%
“…The term confocal refers to the alignment of the light source and the collection system in the same specimen plane. After the laser illuminates the specimen, the tissue emits fluorescence, which is detected by the collection system for image generation (25). The current generation CLE device we used was designed specifically to be integrated into the Bar chart showing a comparison of overall mean (SD) brightness and contrast of in vivo and ex vivo images.…”
Section: Discussionmentioning
confidence: 99%
“…CLE is utilized in the detection of dysplasia, adenoma, and carcinoma. CLE has a high diagnostic accuracy for conditions affecting the gastrointestinal tract, such as esophageal, gastric, and colonic neoplasia, pancreatic cysts and solid lesions, and malignant pancreatobiliary strictures [15]. One single-center study comparing dual-focus narrow band imaging and CLE for realtime diagnosis of adenomatous polyps in patients with FAP, showed that CLE had a similar, high degree of diagnostic value as compared with narrow band imaging [16].…”
Section: Discussionmentioning
confidence: 99%
“…Confocal laser endomicroscopy (CLE) is an advanced endoscopic imaging technology that facilitates the observation of gastrointestinal epithelia at a magnified, cellular level [15]. CLE is utilized in the detection of dysplasia, adenoma, and carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, DEX has been demonstrated to improve pediatric MRI imaging (Mason et al, 2011). Its incorporation into modern clinical imaging workflows will require no modification to imaging technology and would likely be beneficial for physicians, as it would provide additional stabilization for images captured by next-generation endoscopes, colonoscopes, and laparoscopes equipped with cellular-resolution endomicroscopy technologies (Kim et al, 2012; Belykh et al, 2018; Lesur et al, 2019; Yin et al, 2019; Pilonis et al, 2022). However, in clinical settings, there are other methods for regulating the involuntary movement of patients.…”
Section: Discussionmentioning
confidence: 99%